Facing Fake News: The case of the students of the University of the Basque Country - Mendiguren, Terese (2020)
The Internet and social networks have become the most attractive and accessible information channel for young people. Objectives. Examine the behavior of university students when facing fake news and their opinion on this phenomenon. Methodology. Semi-open surveys conducted mainly for Journalism students from the University of the Basque Country. In a second phase, the study was extended to students from other areas of knowledge. Results. Online media use is commonplace for university students and a high percentage of them confess to have been fooled by fake news on at least one occasion. Conclusions and discussion. The students consider they have a high rate of alert when facing fake news. There are some differences, according to the area of ​​knowledge, of the subjects that they consider more invaded by the fake news.